Denaturing Gradient Gel Electrophoresis (DGGE): A Rapid and Sensitive Technique to Screen Nucleotide Sequence Variation in Populations. (November 1999) - Miller, Kristina M.; Ming, Tobi J.; Schulze, Angela D.; Withler, Ruth E.
We describe a rapid and sensitive method for the detection of nucleotide sequence variation that can be used for largescale screening of population markers. Denaturing gradient gel electrophoresis (DGGE) detects sequence variants of amplified fragments by the differences in their melting behavior. DGGE detects most single-base substitutions when carried out on products amplified with a primer to which a GC clamp has been added. Although DGGE has been primarily used for the detection of limited numbers of single-base mutations in disease studies, it offers great potential for use in population analysis of genetic markers with greater levels of sequence variation. The methodology described was developed to identify the number and distribution of MHC class I α1 alleles among chinook salmon ( Oncorhynchus tshawytscha ) populations. DGGE detects 28 of 31 identified α1 sequences, which differ by between 1 and 16 nucleotides and a two-codon indel. By creating a network of control alleles, 22–23 of the MHC alleles can be resolved rapidly and accurately by a single gel run condition, and 27 alleles can be resolved by two gel run conditions. This technique has been used in surveys scoring alleles from two MHC markers (class I α1 and α2) in 20000 individuals of chinook and coho ( O. kisutch ) salmon. A single person in our laboratory now analyzes 160 salmon from one MHC locus per day with DGGE.